NUTRITIONAL STATUS OF ANIMALS IN PERI-URBAN DAIRIES IN PUNJAB STATE OF INDIA - M. P. S. Bakshi; M. Wadhwa; J.S. Hundal (Journal of Animal and Plant Sciences, 2012)
The study was taken up to assess the nutritional status of dairy animals in peri-urban dairies in Punjab State of India. The state Government has established 7 peri-urban dairies; 2 each in Ludhiana and Amritsar and 1 each in Jalandhar, Ferozepur and Hoshiarpur Districts. About 30 dairy houses were selected randomly from each complex. Buffaloes predominated in almost all peri-urban dairies, except in Ferozepur dairy complex (FDC). The animals of FDC had the lowest body weight while animals of Ludhiana downy had highest (478 vs 572 kg) mean weight should be given. The healthy animals of LDC were capable of producing highest (P<0.05) milk. As compare to other groups. The area allocated per adult cattle unit was highest in Jalandhar dairy complex (JDC) and lowest in Ludhiana dairy complex (LDC). However, the space allocated was much lower than the recommended area i.e. 11.25 m2 . Wheat bran was the most common feedstuffs used in the rations of lactating animals. Non-conventional feed resources like brewery and starch industry waste played a significant role in peri-urban dairy production system. The diet of the animal was about 86, 64, 79, 58 and 46% deficient in CP in JDC, ADC, FDC, LDC and HDC respectively while the diet was deficient in fat in almost all dairy houses in all dairy complexes except those of HDC, where only 69% of dairy house fed ration were deficit in fat. The NDF content of the complete feed was higher than the recommended level. The milk urea nitrogen (MUN) was lowest (P<0.05) in animals of FDC (8.1mg/dl) and highest in animals of HDC (20.8mg/dl). The DM offered was about 24, 14, 64, 83 and 50% less than the requirement in dairy houses of the households of JDC, ADC, FDC, LDC and HDC, respectively. The daily consumption of nutrients was lowest (P<0.05) by the animals of LDC and FDC in comparison to animals of other dairy complexes. Only 3.6% of the dairy houses of FDC and 25% of the dairy houses of LDC offered mineral mixture to their animals, while mineral mixture was not offered at all in JDC, ADC and HDC. It was concluded that most of the animals in peri urban dairies were underfed.
Keywords: Nutritional status; Dairy animals; Peri urban dairies